The burden of disease attributable to ambient PM2.5-bound PAHs exposure in Nagpur, India. (August 2018) - Etchie, Tunde O.; Sivanesan, Saravanadevi; Etchie, Ayotunde T.; Adewuyi, Gregory O.; Krishnamurthi, Kannan; George, K.V.; Rao, Padma S.
Abstract: Exposure to PM2.5 -bound polycyclic aromatic hydrocarbons (PAHs) can elicit several types of cancer and non-cancer effects. Previous studies reported substantial burdens of PAH-induced lung cancer, but the burdens of other cancer types and non-cancer effects remain unknown. Thus, we estimate the cancer and non-cancer burden of disease, in disability-adjusted life years (DALYs), attributable to ambient PM2.5 -bound PAHs exposure in Nagpur district, India, using risk-based approach. We measured thirteen PAHs in airborne PM2.5 sampled from nine sites covering urban, peri-urban and rural areas, from February 2013 to June 2014. We converted PAHs concentrations to benzo[a]pyrene equivalence (B[a]Peq ) for cancer and non-cancer effects using relative potency factors, and relative toxicity factors derived from quantitative structure-activity relationships, respectively. We calculated time-weighted exposure to B[a]Peq, averaged over 30 years, and adjusted for early-life susceptibility to cancer. We estimated the DALYs/year using B[a]Peq exposure levels, published toxicity data, and severity of the diseases from Global Burden of Disease 2016 database. The annual average concentration of total PM2.5 -bound PAHs was 458 ± 246 ng/m 3 and resulted in 49, 500 DALYs/year (0.011 DALYs/person/year). The PAH-related DALYs followed this order: developmental (mostly cardiovascular) impairments (55.1%) > cancer (26.5%) or lung cancer (23.1%) > immunological impairments (18.0%) > reproductive abnormalities (0.4%). Graphical abstract: The burden of specific disease (DALYs/year) attributable to ambient PM2.5 -bound PAHs exposure in Nagpur district, India. Image 1 Highlights: We assessed PM2.5–bound PAHs in urban, peri-urban and rural areas of Nagpur. We estimated the DALYs/year resulting from the PAHs exposure. Average annual levels of total PM2.5–bound PAHs in Nagpur was 458 ± 246 ng/m3. The PAHs exposure caused about 49500 DALYs, annually. PAH-related burden from developmental impairments was the largest.